Democratic crises; the bane of developmental local government in Nigeria - Adetiba, Toyin Cotties; Adedokun, Olusegun Jonathan (Technium Social Sciences Journal, 2021)
In the cycle of scholars on Nigeria’s local government system, the belief is that Nigeria has only succeeded in transiting to a system that represents a synthesis of various influences, in which formal democratic institutions of democracy are a smokescreen for informal institutions which preserve anti-democratic practices and power relationships in local government administration. Thus making them incapable of performing their developmental roles as the third tier government, yet overstrained with many socio-political and economic responsibilities they have never been able to implement. The Nigerian 1976 Local Government Reform was geared towards making local government a bedrock for socio-economic and political development. But the 1999 constitution seems to have overridden the gains and aspirations of this tier of government while undermining peoples’ aspirations as well as the efficacy of grassroots governance. Using qualitative method, this study examines the state of local government in Nigeria and the factors militating against its developmental status and concludes that the nature and democratic characters of the Nigerian state explains the ineffectiveness of local government in Nigeria. Keywords: Local Government, Constitution, Developmental, Administration, Grassroots